Vacuum‐Deposited Inorganic Perovskite Light‐Emitting Diodes with External Quantum Efficiency Exceeding 10% via Composition and Crystallinity Manipulation of Emission Layer under High Vacuum - Chung‐An Hsieh; Guang‐Hsun Tan; Yung‐Tang Chuang; Hao‐Cheng Lin; Po‐Ting Lai; Pei‐En Jan; Bo‐Han Chen; Chih‐Hsuan Lu; Shang‐Da Yang; Kai‐Yuan Hsiao; Ming‐Yen Lu; Li‐Yin Chen; et al. (Advanced Science, 2023)
Abstract Although vacuum‐deposited metal halide perovskite light‐emitting diodes (PeLEDs) have great promise for use in large‐area high‐color‐gamut displays, the efficiency of vacuum‐sublimed PeLEDs currently lags that of solution‐processed counterparts. In this study, highly efficient vacuum‐deposited PeLEDs are prepared through a process of optimizing the stoichiometric ratio of the sublimed precursors under high vacuum and incorporating ultrathin under‐ and upper‐layers for the perovskite emission layer (EML). In contrast to the situation in most vacuum‐deposited organic light‐emitting devices, the properties of these perovskite EMLs are highly influenced by the presence and nature of the upper‐ and presublimed materials, thereby allowing us to enhance the performance of the resulting devices. By eliminating Pb° formation and passivating defects in the perovskite EMLs, the PeLEDs achieve an outstanding external quantum efficiency (EQE) of 10.9% when applying a very smooth and flat geometry; it reaches an extraordinarily high value of 21.1% when integrating a light out‐coupling structure, breaking through the 10% EQE milestone of vacuum‐deposited PeLEDs.